2015
DOI: 10.1039/c5fo00397k
|View full text |Cite
|
Sign up to set email alerts
|

Theobromine inhibits differentiation of 3T3-L1 cells during the early stage of adipogenesis via AMPK and MAPK signaling pathways

Abstract: Obesity is characterized by hypertrophy and/or by the differentiation or adipogenesis of pre-existing adipocytes. In this study, we investigated the inhibitory effects of theobromine, a type of alkaloid in cocoa, on adipocyte differentiation of 3T3-L1 preadipocytes and its mechanisms of action. Theobromine inhibited the accumulation of lipid droplets, the expression of PPARγ and C/EBPα, and the mRNA expression of aP2 and leptin. The inhibition of adipogenic differentiation by theobromine occurred primarily in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
48
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 45 publications
6
48
1
Order By: Relevance
“…8 Furthermore, recent studies showed that the induction of the cell cycle arrest at the G0/G1 phase suppresses MCE, resulting in the inhibition of adipogenesis. [37][38][39] Here, we also found that ezetimibe could arrest the cell cycle at the G0/G1 phase, which induced the AMPK-dependent inhibition of cell proliferation dependently on AMPK in the early stage of adipogenesis. [37][38][39] Here, we also found that ezetimibe could arrest the cell cycle at the G0/G1 phase, which induced the AMPK-dependent inhibition of cell proliferation dependently on AMPK in the early stage of adipogenesis.…”
Section: Discussionsupporting
confidence: 58%
“…8 Furthermore, recent studies showed that the induction of the cell cycle arrest at the G0/G1 phase suppresses MCE, resulting in the inhibition of adipogenesis. [37][38][39] Here, we also found that ezetimibe could arrest the cell cycle at the G0/G1 phase, which induced the AMPK-dependent inhibition of cell proliferation dependently on AMPK in the early stage of adipogenesis. [37][38][39] Here, we also found that ezetimibe could arrest the cell cycle at the G0/G1 phase, which induced the AMPK-dependent inhibition of cell proliferation dependently on AMPK in the early stage of adipogenesis.…”
Section: Discussionsupporting
confidence: 58%
“…has described an inhibitory role for THB on adipogenesis by the murine stromal adipocyte-progenitor cell line 3T3-L1 [42]. This is interesting in the context of the results presented here because the pathways that regulate adipogenesis and osteogenesis in mammalian cells are antagonistic to one another [32, 4348].…”
Section: Discussionsupporting
confidence: 51%
“…Western blot analysis. Western blot analysis was performed by a modification of the technique described previously (Jang et al, 2015). Whole cell lysates were prepared by lysing cells in lysis buffer (150 mM NaCl, 2 mM EDTA, 1% NP-40, 0.5% sodium deoxycholate, 0.1% SDS, 50 mM Tris-Cl, 1 mM phenylmethylsulfonyl fluoride).…”
Section: Measurement Of Immunoglobulin E and Cytokine Levelmentioning
confidence: 99%